2015
DOI: 10.1149/2.0181508jss
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron White-Beam X-Ray Topography Analysis of the Defect Structure of HVPE-GaN Substrates

Abstract: The defect structure of HVPE-GaN crystals is examined using synchrotron white-beam X-ray topography (SWXRT) and topography results are interpreted and discussed in comparison to reciprocal lattice point broadening from high resolution X-ray diffraction (HRXRD) measurements. Two as-received commercial HVPE-GaN wafers from two different vendors and one HVPE-GaN which was grown on an ammonothermal GaN-seed are investigated in this study. To our knowledge SWXRT large area back-reflection analysis of HVPE-GaN grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…RSM measurements of the GaN homo-epitaxial layer were generally performed to determine the lattice parameter, homogeneity and the crystallinity along the off-specular direction. 35,36 The calculated extinction distance was 1.3 µm at the 1122 Bragg reflection based on dynamical X-ray diffraction theory. 37,38 Figures 4(c) and (d) show the HK mesh scan near the 1122 Bragg reflection.…”
Section: Aip Advances 8 075318 (2018)mentioning
confidence: 99%
“…RSM measurements of the GaN homo-epitaxial layer were generally performed to determine the lattice parameter, homogeneity and the crystallinity along the off-specular direction. 35,36 The calculated extinction distance was 1.3 µm at the 1122 Bragg reflection based on dynamical X-ray diffraction theory. 37,38 Figures 4(c) and (d) show the HK mesh scan near the 1122 Bragg reflection.…”
Section: Aip Advances 8 075318 (2018)mentioning
confidence: 99%
“…One can say that this homogeneity concerns the high dislocation density of the HVPE material grown on foreign seeds. It was shown that in commercially available HVPE-GaN the dislocation rearrangement into cell networks can take place under external or internal stress in the course of plastic relaxation [ 43 ]. The Borrmann effect can therefore hardly be observed in HVPE-GaN grown on foreign substrates due to the low material quality; it is nearly extinct.…”
Section: Discussionmentioning
confidence: 99%
“…By magnifying the image through a lens and using a phosphor CCD detector, we expect to be able to achieve high image resolution; however, we may not see the overall feature on the wafer scale. The misorientation deformation (mosaicity) and dislocations in GaN are shown using synchrotron white-beam x-ray topography (SWXRT) on a GaN substrate using back reflection Laue geometry [29]. The report does not show the lattice tilting on a wafer scale even though they adopted section transmission geometry, which means that we improve the SWXRT technique for the observation of tilting on the wafer scale in the current work.…”
Section: -3mentioning
confidence: 94%